2017
DOI: 10.1002/jnr.24054
|View full text |Cite
|
Sign up to set email alerts
|

Development of a systems‐based in situ multiplex biomarker screening approach for the assessment of immunopathology and neural tissue plasticity in male rats after traumatic brain injury

Abstract: Traumatic brain injuries (TBI) pose a massive burden of disease and continue to be a leading cause of morbidity and mortality throughout the world. A major obstacle in developing effective treatments is the lack of comprehensive understanding of the underlying mechanisms that mediate tissue damage and recovery after TBI. As such, our work aims to highlight the development of a novel experimental platform capable of fully characterizing the underlying pathobiology that unfolds post-TBI. This platform encompasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…3a). Then, signal corrections are performed, providing seamless 10-100 plex mosaics of whole-brain slices that provide sufficient spatial extent and spatial resolution to reveal cellular structures 12,13 . Importantly, they are suitable for automated scoring, for identifying a rich diversity of cell types (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a). Then, signal corrections are performed, providing seamless 10-100 plex mosaics of whole-brain slices that provide sufficient spatial extent and spatial resolution to reveal cellular structures 12,13 . Importantly, they are suitable for automated scoring, for identifying a rich diversity of cell types (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This work has shown that in both the spinal cord and brain, a key mitochondrial multienzyme complex, OGDHC, is downregulated as a chronic consequence of severe SCI, with the downregulation linked to decreased activity of the immediate metabolic partner of OGDHC—GDH. The extension of the spinal trauma consequences to the distant area of CNS should be taken into account in the studies which develop the damage markers of neurotrauma, using non-damaged area of the same organism as a matched control ( Bogoslovsky et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…22 More advanced computational solutions are also being developed that will employ machine learning algorithms customized to our imaging paradigm, ultimately enabling easily scalable image data analysis to support systems biology and translational research into devising optimal treatment strategies to reduce the burden of neurological disease/ disorders and/or traumatic insults. 23 Computational advances, in combination with future mechanical automation of the sample preparation, can improve the scalability of this methodology so that it may be routinely performed on patients monitored for treatment response after virotherapy or other immunotherapies. 24 Increased application of our novel in situ multiplex immunofluorescence will also promote an improved understanding of the range of immune and tumor cell response to virotherapy, and with clinical correlation will provide biological insights in patient stratification and monitoring response to treatment.…”
Section: Discussionmentioning
confidence: 99%